2011
DOI: 10.1007/s10562-011-0711-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si-Doping on Thermal Stability and Diesel Oxidation Activity of Pt Supported Porous γ-Al2O3 Monolithic Catalyst

Abstract: A series of different contents of Si-stabilized aluminas with high thermal stability were synthesized by the coprecipitation method and were used as the support of Pt diesel oxidation catalysts. The physicochemical properties of SiO 2 -Al 2 O 3 (SA) and the catalytic performance of Pt/SiO 2 -Al 2 O 3 (Pt/SA) were characterized in detail by TG-DTA, XRD, infrared spectroscopy, N 2 adsorption, NMR, CO-TPD, and the catalytic activity evaluation of CO and C 3 H 6 oxidations as well as NO reduction in simulating die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…First, NaAlO 2 solution (80 g L À1 , a k ¼ 1.42) was prepared by adding Al(OH) 3 into 300 mL NaOH solution (62 g L À1 ) at 100 C. And then, the resultant NaAlO 2 solution and Al 2 (SO 4 ) 3 solution (342 g L À1 ) were together dropped into distilled water at 60 C slowly under vigorous magnetic stirring. The white precipitation formed at the required pH value (6)(7)(8)(9)(10)(11) and aged for 2 h at 90 C under strong stirring. The solid product was collected by lter and washed by hot water (90 C) for several times, following dried at 110 C, which are marked as B-x (x ¼ the corresponding pH value).…”
Section: Synthesis Of Boehmite Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, NaAlO 2 solution (80 g L À1 , a k ¼ 1.42) was prepared by adding Al(OH) 3 into 300 mL NaOH solution (62 g L À1 ) at 100 C. And then, the resultant NaAlO 2 solution and Al 2 (SO 4 ) 3 solution (342 g L À1 ) were together dropped into distilled water at 60 C slowly under vigorous magnetic stirring. The white precipitation formed at the required pH value (6)(7)(8)(9)(10)(11) and aged for 2 h at 90 C under strong stirring. The solid product was collected by lter and washed by hot water (90 C) for several times, following dried at 110 C, which are marked as B-x (x ¼ the corresponding pH value).…”
Section: Synthesis Of Boehmite Precursorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For some specific applications, such as catalytic conversion of automotive emission gas, 8 diesel catalytic oxidation, 9 catalytic decomposition of propellants for space propulsion, 10 the ability of γ-Al2O3 to maintain large specific surface area and abundant catalytically active surface sites at 1100~1200 °C or even higher temperature is of vital importance, which will allow for well-dispersion of active precious metal catalytic components and the enhanced catalytic activity. [1][2][3][4][5][6][7] For some specific applications, such as catalytic conversion of automotive emission gas, 8 diesel catalytic oxidation, 9 catalytic decomposition of propellants for space propulsion, 10 the ability of γ-Al2O3 to maintain large specific surface area and abundant catalytically active surface sites at 1100~1200 °C or even higher temperature is of vital importance, which will allow for well-dispersion of active precious metal catalytic components and the enhanced catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, γ-Al 2 O 3 can be sintered easily and can transform to thermodynamically stable Al 2 O 3 under high temperatures, resulting in the loss of surface area. In order to solve this problem, many additives, such as lanthanum nitrate [12,13] , cerium nitrate [14] , zirconium nitrate [14] , phosphoric acid [15] and tetraethyl orthosilicate(TEOS) [16] have been added to γ-Al 2 O 3 by conventional impregnation, precipitation or sol-gel method. The introduction of lanthanum can convert the pentacoordinated aluminum ions of γ-Al 2 O 3 into octahedral ones and improve the thermal stability of γ-Al 2 O 3 [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Although it was reported that ZrO2, TiO2, SiO2, and their mixed oxides show good sulfur tolerance, [21][22][23][24][25] few attempts have been done on improving sulfur resistibility of recent extensively used CeO2-ZrO2-Al2O3 based commercial DOCs. Due to the fact that SiO2 shows good sulfur tolerance and texture properties, the purpose of this work is to enhance the sulfur resistance of Pt-Pd/CeO2-ZrO2-Al2O3 commercial DOC using surface cladding of SiO2.…”
Section: Introductionmentioning
confidence: 99%